Upscaling, toxicity and efficacy of multifaceted dressing embedded with dsirna-loaded gold nanoparticles for enhancing diabetic wound treatment - Farha Yasmin Faris Taufeq; Muhammad Luqman Nordin; Haliza Katas (PLoS ONE, 2025)
Poor vascularization and infections hinder diabetic wound healing, posing challenges in therapy development. A multi-action approach incorporating Dicer-substrate small interfering RNA (DsiRNA) against the prostaglandin transporter (PGT) gene and gold nanoparticles (AuNPs) into a Pluronic F-127 (PF127) gel was developed. This study aimed to upscale AuNP biosynthesis using Lignosus rhinocerotis (tiger milk mushroom, TMM) extract and chitosan as stabilizers. Response Surface Methodology (RSM) optimized the synthesis with 0.6 mL chloroauric acid (HAuCl₄) and 4.4 mL TMM extract, producing upscaled AuNPs (152.93 ± 1.56 nm, + 30 mV) with a Surface Plasmon Resonance peak at 538 nm. Both lab-scale and upscaled AuNPs exhibited antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa (MIC: 250 μg/mL). The gel formulation demonstrated favourable gelling properties for wound dressing. A 28-day toxicity study confirmed no adverse effects on haematology, biochemistry, or organ morphology. In diabetic Wistar rats, only the wounds treated with Pluronic gels containing AuNPs-DsiRNA showed no signs of infection, while the other groups exhibited infection and pustules in the wounded areas. These findings highlight the potential of AuNP-DsiRNA thermoresponsive gels as an innovative, safe, and effective therapy for diabetic wound healing.